Feasibility of Shear Wave Elastography Imaging for Evaluating the Biological Behavior of Breast Cancer - Liu, Chaoxu; Zhou, Jin; Chang, Cai; Zhi, Wenxiang (Frontiers in Oncology, 2022)
Objective To explore the feasibility of shear wave elastography (SWE) parameters for assessing the biological behavior of breast cancer Methods In this prospective study, 224 breast cancer lesions in 216 female patients were examined by conventional ultrasound and shear wave elastography in sequence. The maximum size (Smax) of the lesion was measured by conventional ultrasound, and then shear wave elastography was performed on this section to obtain relevant parameters, including maximum elasticity (Emax), mean elasticity (Emean), standard deviation of elasticity (SD), and the area ratio of shear wave elastography to conventional ultrasound (AR). The relationship between SWE parameters and pathological type, histopathological classification, histological grade, lymphovascular invasion status (LVI), axillary lymph node status (ALN) and immunohistochemistry of breast cancer lesions was performed according to postoperative pathology. Results In the univariate analysis, the pathological type and histopathological classification of breast cancer were not significantly associated with SWE parameters; with an increase in the histological grade of invasive ductal carcinoma (IDC), SD (P=0.016) and Smax (P=0.000) values raised. In the ALN-positive group，Smax (P=0.004) was significantly greater than in the ALN-negative group; Smax (P=0.003), Emax (P=0.034) and SD (P=0.045) were significantly higher in the LVI-positive group than in the LVI-negative group; SD (P=0.043, P=0.047) and Smax (P=0.000, P=0.000) were significantly lower in the ER+ and PR+ groups than in the ER- and PR- groups, respectively; AR (P=0.032) was significantly higher in the ER+ groups than in the ER- groups. and Smax (P=0.002) of the HER2+ group showed higher values than that of the HER2- group; Smax (P=0.000), SD (P=0.006) and Emax (P=0.004) of the Ki-67 high-expression group showed significantly higher values than of the Ki-67 low-expression group. In the multivariate analysis, Ki-67 was an independent factor of Smax (P=0.005), Emax (P=0.004) and SD (P=0.006); ER was independent influencing factors of Smax (P=0.000) and AR (P=0.032). LVI independently influence Smax (P=0.006). Conclusions The SWE parameters Emax, SD and AR can be used to evaluate the biological behavior of breast cancer.